FAKTOR YANG BERHUBUNGAN DENGAN RESPON MASYARAKAT TERHADAP PROGRAM VAKSIN COVID-19 DI RW 001 KELURAHAN BOJONG RAWALUMBU, KOTA BEKASI TAHUN 2021 - Alya Zahra Hamidah, (2022)
Covid-19 vaccination program outlined by the government shows various responses from the public. The 70% percentage targeted by the government for each region can be achieved through cooperation from various levels especially the RW level that can move quickly in influencing the community response in its region. This study aims to determine the factors associated with community's response to Covid-19 vaccination in RW 001, Bojong Rawalumbu Village, Bekasi City. The research method used on this study is a quantitative design with a cross-sectional approach. The study was conducted in December 2021 with samples of 358 respondents. Sampling was performed purposively sampling with a 17-64 age range. Data collection was conducted using an online questionnair. The data obtained analyzed using univariate and bivariate analysis. The results of the bivariate analysis used chi-square test showed that there was a relationship between age (p-value = 0.04); employment (p-value = 0.049); vaccine effectiveness (p-value = 0.041); chronic disease (p-value = 0.000); and perceived susceptibility (p-value = 0.049) to the response shown by the community to the Covid-19 vaccination program. The results of this study are expected to be used as the basis for education and policy making from the lowest level, which is the RW level related to the prevention of Covid-19 through the vaccine program. Keywords: Covid-19, vaccination program, community response